The analogy and peculiarity of the «Кемпірқосақ» alternative in relatives and foreign languages - Оtelbay Г. Т. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The article is devoted to the history of the emergence of the Kazakh word «kempirqosaq», that is, the rainbow. The author considers, collates, compares the meanings of the word in German, English, French and Turkic languages.